Efektivitas Perda No. 4 Tahun 2018 Tentang Pajak Sarang Burung Walet - Sukriansyah Sukriansyah; Ahmadi Ahmadi (QAIMUDDIN: Journal of Constitutional Law Review, 2021)
ABSTRACTThis study aims to determine the effectiveness of PERDA No. 4 of 2018 concerning Swallow's Nest Tax in Bombana Regency, Poleang Timur District. Materials obtained from interviews conducted in the field. The methods of collecting materials used in this study were observation, interviews, and documentation. The material analysis methods used in this study are material reduction, material display, and material verification. Based on the results of the research conducted, it shows that the swallow's nest business in Poleang Timur District is growing rapidly where the income of swallow entrepreneurs is already high and the effectiveness of PERDA No. 4 of 2018 concerning the Swallow's Nest Tax in Bombana Regency, Poleang Timur District, reaped various problems among the government and swallow entrepreneurs from this problem. and the absence of government contributions to swallow nest entrepreneurs. So to optimize the implementation, the Bombana Regency government made efforts, namely: Conducting door-to-door outreach and conducting data collection for swallow nest entrepreneurs. Researchers provide recommendations to local governments to revisit and revise related to the issue of the amount of tax collection and provide assistance in the form of medicines and others.   ABSTRACTThis study aims to determine the effectiveness of PERDA No. 4 of 2018 concerning Swallow's Nest Tax in Bombana Regency, Poleang Timur District. Materials obtained from interviews conducted in the field. The methods of collecting materials used in this study were observation, interviews, and documentation. The material analysis methods used in this study are material reduction, material display, and material verification. Based on the results of the research conducted, it shows that the swallow's nest business in Poleang Timur District is growing rapidly where the income of swallow entrepreneurs is already high and the effectiveness of PERDA No. 4 of 2018 concerning the Swallow's Nest Tax in Bombana Regency, Poleang Timur District, reaped various problems among the government and swallow entrepreneurs from this problem. and the absence of government contributions to swallow nest entrepreneurs. So to optimize the implementation, the Bombana Regency government made efforts, namely: Conducting door-to-door outreach and conducting data collection for swallow nest entrepreneurs. Researchers provide recommendations to local governments to revisit and revise related to the issue of the amount of tax collection and provide assistance in the form of medicines and others.